Infection or autoinflammatory disease? Difficulties of differential diagnosis on the example of a carrier of the Q705K variant of the NLRP3 gene - A. S. Levina; N. V. Skripchenko; O. V. Goleva (Журнал инфектологии, 2025)
The Q705K variant of the NLRP3 gene is considered a variant of uncertain significance and a risk factor contributing to the autoinflammatory disease phenotype. To present a clinical picture of the disease in a pediatric patient carrying the Q705K variant of the NLRP3 gene with a diagnosed cryopyrin-associated periodic syndrome. A 10-year-old child with frequent episodes of fever, refractory to antipyretic therapy, with urticaria, enlarged cervical lymph nodes, manifestations of pharyngitis and frequent respiratory diseases was examined. 338 genes associated with primary immunodeficiency have been analyzed by targeted multigene sequencing. Variant c.2113C>A (p. Gln705Lys) of the NLRP3 gene in a heterozygous state has been identified. The results of laboratory and instrumental research methods during several hospitalizations are analyzed. During hospitalizations with febrile episodes the child was diagnosed, as a rule, with infectious exanthems (yersiniosis, parvovirus, enterovirus, infectious mononucleosis). Chronic persistent herpes type 6 and Epstein-Barr viral infection and a deficiency of cellular immunity have been confirmed. Despite the positive results of the etiological methods, on the example of the last hospitalization - contradictory and not consistent with the clinical picture, given the long history of regular febrile episodes of the same type, accompanied by rashes, a cold reaction, and the identification of an uncertain clinical significance of the NLRP3 gene Q705K in accordance with the accepted diagnostic criteria a child at the age of 18 was diagnosed with cryopyrin-associated periodic syndrome.In a situation of repeated episodes of the same type of febrile disease, the identification of infection markers, especially markers of opportunistic infections, does not exclude autoinflammatory syndrome.